IMPLEMENTATION OF ETHICS BUSINESS SHARIA IN BUSINESS ACTOR PERFORMANCE MICRO, SMALL, AND INTERMEDIATE IN THE TRADE SECTOR - Mahsuni, Abdul Wahid (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
Islamic business ethics itself carries principles that distinguish between good and bad actions in business activities, guided by Sharia and Islamic teachings. Business ethics is responsible for defining the moral standards and expected behaviours of players in the business world. In the context of Micro, Small, and Medium Enterprises (MSMEs) in the trade sector, business ethics plays a crucial role in creating a fair and honest business environment that enhances consumer trust in the products and services offered. This study aims to analyse the implementation of Shariah business ethics on the performance of MSMEs in the trade sector. The research method used is qualitative. The findings indicate that business ethics has a significantly strong influence on MSME performance